2012
DOI: 10.3109/14767058.2012.733778
|View full text |Cite
|
Sign up to set email alerts
|

Early neonatal outcomes of volume guaranteed ventilation in preterm infants with respiratory distress syndrome

Abstract: In conclusion, VG ventilation in combination with surfactant treatment significantly reduced both duration of mechanical ventilation and early neonatal oxygen related morbidities including BPD, ROP and IVH in preterm infants with RDS. This data favors the use of VG ventilation in respiratory support of premature infants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 28 publications
1
21
1
Order By: Relevance
“…Data reporting the length of mechanical ventilation in VTV and PLV groups are described in nine trials 19 21 24–26 29 31 33 35. The meta-analysis revealed a mathematical MD of −2.0 (−3.14 to −0.86) days reduced duration of ventilation using VTV (figure 5).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Data reporting the length of mechanical ventilation in VTV and PLV groups are described in nine trials 19 21 24–26 29 31 33 35. The meta-analysis revealed a mathematical MD of −2.0 (−3.14 to −0.86) days reduced duration of ventilation using VTV (figure 5).…”
Section: Resultsmentioning
confidence: 99%
“…Data reporting supplemental oxygen administration in VTV and PLV groups are described in two trials 21 27. The meta-analysis revealed a mathematical MD of −1.68 (−2.47 to −0.88) days reduced supplemental oxygen administration using VTV compared to PLV (table 2).…”
Section: Resultsmentioning
confidence: 99%
“…Herein, pneumothorax proved to be less likely in the VG group. A well-organized Cochrane review concluded lower mortality after receiving ventilation with VG (7), while Guven et al, found no significant decrease in death rate after volume-controlled ventilation (10). Nevertheless, no differences could be observed between the survival rates of the two groups.…”
Section: Discussionmentioning
confidence: 99%
“…Since safe level of oxygen saturation differs with postmenstrual age and stage of ROP, no fixed SpO 2 range is recommended so far (9). Lower SpO 2 level in early days of life could roughly have a preventive effect on ROP; though it increased death rates in several studies (10). Although avoidance of alteration between hypoxia and hyperoxia seems to be one of the desirable methods to decrease ROP, the benefits should be balanced against the risk of mortality and other morbidities such as cerebral palsy (11,12).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation